3D Printing: Applications in Tissue Engineering, Medical Devices, and Drug Delivery - Pavan Kalyan, BG; Kumar, Lalit (AAPS PharmSciTech, 2022)
The gemstone of 3-dimensional (3D) printing shines up from the pyramid of additive manufacturing. Three-dimensional bioprinting technology has been predicted to be a game-changing breakthrough in the pharmaceutical industry since the last decade. It is fast evolving and finds its seats in a variety of domains, including aviation, defense, automobiles, replacement components, architecture, movies, musical instruments, forensic, dentistry, audiology, prosthetics, surgery, food, and fashion industry. In recent years, this miraculous manufacturing technology has become increasingly relevant for pharmaceutical purposes. Computer-aided drug (CAD) model will be developed by computer software and fed into bioprinters. Based on material inputs, the printers will recognize and produce the model scaffold. Techniques including stereolithography, selective laser sintering, selective laser melting, material extrusion, material jetting, inkjet-based, fused deposition modelling, binder deposition, and bioprinting expedite the printing process. Distinct advantages are rapid prototyping, flexible design, print on demand, light and strong parts, fast and cost-effective, and environment friendly. The present review gives a brief description of the conceptional 3-dimensional printing, followed by various techniques involved. A short note was explained about the fabricating materials in the pharmaceutical sector. The beam of light is thrown on the various applications in the pharma and medical arena.